Choice of outcomes and measurement instruments in randomised trials on eLearning in medical education : a systematic mapping review protocol - Law, Gloria Chunyi (2018)
Background: There will be a lack of 18 million healthcare workers by 2030. Multiplying the number of well-trained healthcare workers through innovative ways such as eLearning is highly recommended in solving this shortage. However, high heterogeneity of learning outcomes in eLearning systematic reviews reveals a lack of consistency and agreement on core learning outcomes in eLearning for medical education. In addition, there seems to be a lack of validity evidence for measurement instruments used in these trials. This undermines the credibility of these outcome measures and affects the ability to draw accurate and meaningful conclusions. The aim of this research is to address this issue by determining the choice of outcomes, measurement instruments and the prevalence of measurement instruments with validity evidence in randomised trials on eLearning for pre-registration medical education. Methods: We will conduct a systematic mapping and review to identify the types of outcomes, the kinds of measurement instruments and the prevalence of validity evidence among measurement instruments in eLearning randomised controlled trials (RCTs) in pre-registration medical education. The search period will be from January 1990 until August 2017. We will consider studies on eLearning for health professionals’ education. Two reviewers will extract and manage data independently from the included studies. Data will be analysed and synthesised according to the aim of the review. Discussion: Appropriate choice of outcomes and measurement tools is essential for ensuring high-quality research in the field of eLearning and eHealth. The results of this study could have positive implications for other eHealth interventions, including (1) improving quality and credibility of eLearning research, (2) enhancing the quality of digital medical education and (3) informing researchers, academics and curriculum developers about the types of outcomes and validity evidence for measurement instruments used in eLearning studies. The protocol aspires to assist in the advancement of the eLearning research field as well as in the development of high-quality healthcare professionals’ digital education.